The Effect of Islamic Financing on the Growth of Micro, Small and Medium Enterprises in Indonesia - Judijanto, Loso; Mu'min, Halek (West Science Islamic Studies, 2024)
This study investigates the impact of Islamic financing on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Utilizing a quantitative approach, the research involved 110 MSMEs that have accessed Islamic financing products. Data were collected using a structured questionnaire and analyzed through SPSS version 26, employing correlation and multiple regression analyses. The study focuses on three key growth indicators: profitability, market expansion, and operational efficiency. The results reveal that Islamic financing has a significant positive impact on all three indicators, with the strongest effect observed on operational efficiency. These findings highlight the potential of Islamic financing to promote MSME growth in Indonesia, providing valuable insights for policymakers, financial institutions, and business owners. The study contributes to the growing body of literature on Islamic finance and its role in supporting sustainable business practices.